How might degrees of belief shift? On action conflicting with professed beliefs. (3rd July 2016) - Rowbottom, Darrell P.
Abstract: People often act in ways that appear incompatible with their sincere assertions (such as trembling in fear when their death becomes an imminent possibility, despite earlier professing that "Death is not bad!"). But how might we explain such cases? On the shifting view, subjects' degrees of belief (or degrees of confidence) may be highly sensitive to changes in context. This paper articulates and refines this view, after defending it against recent criticisms. It details two mechanisms by which degrees of beliefs may shift.